BUYA HAMKA’S SUFI THOUGHT AND ITS RELEVANCE TO ISLAMIC EDUCATION IN INDONESIA - Syam, Aldo Redho; Diningrat, Idharul Haq Jaya; Susanto, Happy; Asrori, Asrori (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Buya Hamka’s Sufi thought revitalizes modern Islamic education in Indonesia by promoting “active Sufism”—a spirituality deeply rooted in ethical values and social responsibility. His approach transcends mere intellectual learning, fostering holistic character development that balances intellect, emotion, and spirituality. This framework addresses contemporary moral challenges, making Hamka’s Sufism highly relevant for shaping well-rounded, socially engaged Muslim individuals today. This study aims to analyze Hamka’s Sufi thought and its relevance to Islamic education in Indonesia. Employing a qualitative approach in the form of a literature study, the research focuses on Hamka’s major writings. Data were analyzed through thematic identification, categorization of key dimensions, and synthesis of findings, with validation ensured through source triangulation. The results reveal that This study explores Buya Hamka’s concept of Sufism and its relevance to Islamic education in Indonesia. Hamka integrates faith, moral, and spiritual education into a holistic framework that addresses contemporary challenges faced by Muslim communities. His approach emphasizes nurturing strong faith (iman) through spiritual practices like dhikr and tafakkur, fostering moral character based on divine ethics, and cultivating spiritual consciousness (taqwa) for inner transformation. Central to Hamka’s philosophy is the dual goal of achieving happiness in both worldly and spiritual realms, promoting a balanced life that combines ethical responsibility with practical engagement. This research highlights Hamka’s educational vision as a dynamic model that unites intellectual growth with spiritual and moral development. The study’s novelty lies in framing Hamka’s Sufism as a contextually relevant pedagogy, capable of guiding holistic human development in modern Islamic education in Indonesia, thereby addressing gaps between tradition and contemporary educational needs.